PEG-based thermosensitive and biodegradable hydrogels - Shi, Jiayue; Yu, Lin; Ding, Jiandong (Acta biomaterialia, 2021)
Injectable thermosensitive hydrogels are free-flowing polymer solutions at low or room temperature, making them easy to encapsulate the therapeutic payload or cells via simply mixing. Upon injection into the body, in situ forming hydrogels triggered by body temperature can act as drug-releasing reservoirs or cell-growing scaffolds. Finally, the hydrogels are eliminated from the administration sites after they accomplish their missions as depots or scaffolds. This review outlines the recent progress of poly(ethylene glycol) (PEG)-based biodegradable thermosensitive hydrogels, especially those composed of PEG-polyester copolymers, PEG-polypeptide copolymers and poly(organophosphazene)s. The material design, performance regulation, thermogelation and degradation mechanisms, and corresponding applications in the biomedical field are summarized and discussed. A perspective on the future thermosensitive hydrogels is also highlighted. Thermosensitive hydrogels undergoing reversible sol-to-gel phase transitions in response to temperature variations are a class of promising biomaterials that can serve as minimally invasive injectable systems for various biomedical applications. Hydrophilic PEG is a main component in the design and fabrication of thermoresponsive hydrogels due to its excellent biocompatibility. By incorporating hydrophobic segments, such as polyesters and polypeptides, into PEG-based systems, biodegradable and thermosensitive hydrogels with adjustable properties in vitro and in vivo have been developed and have recently become a research hotspot of biomaterials. The summary and discussion on molecular design, performance regulation, thermogelation and degradation mechanisms, and biomedical applications of PEG-based thermosensitive hydrogels may offer a demonstration of blueprint for designing new thermogelling systems and expanding their application scope. [Display omitted]